Burial with a chariot at the Tabyldy cemetery, Central Kazakhstan - Kukushkin, I.A.; Dmitriev, E.A. (Archaeology, Ethnology and Anthropology of Eurasia, 2019)
This article describes a high-ranking burial at the Tabyldy cemetery in the Shetsky District of the Karaganda Region, Kazakhstan. The mound was encircled with a stone enclosure and marked a double burial of horses with discoid cheekpieces and metal staples, symbolizing a chariot. Funerary items include a bronze knife-dagger, a goad-head, a metal pendant from a plate twisted 1.5 times and overlaid with gold, paste beads, tubular beads, and potsherds. A detailed description of these items is provided. The cheek-pieces resemble those of the Staroyuryevo type. Their position on the skulls of the horses suggests a reconstruction of the harness. On the basis of new fi nds, the evolution of the cheek-pieces is proposed. The reconstructed severe bits were made by interweaving metal staples with leather strips. This innovation, securing better driving, was the reason why later cheek-pieces had no studs. A comparative analysis of the burial rite and funerary items suggests an Early Alakul attribution. The fact that the horses’ heads were oriented to the northeast, like those of the buried humans (judging by the places where the bottoms of ceramic vessels were concentrated), evidences the infl uence of the Early Timber-Grave (Pokrovsk) culture. The AMS date and its 1 SD limits point to the late 18th to early 17th century BC, suggesting the Nurtai stage of the Alakul culture in Central Kazakhstan.
Keywords: Central Kazakhstan; Bronze Age; Early Alakul culture; chariot harness; discoid cheek-pieces; bits